Mispronunciation Detection and Diagnosis Through a Chatbot - Martinez Quezada, Marcos Eduardo; Lopez Orozco, Francisco; Olmos Sanchez, Karla Miroslava; Sánchez Solís, Julia Patricia (IGI GLOBAL, 2020)
The interaction between humans and machines has evolved; thus, the idea of being able to communicate with computers as we usually do with other people is becoming increasingly closer to coming true. Nowadays, it is common to come across intelligent systems named chatbots, which allow people to communicate by using natural language to hold conversations related to a specific domain. Chatbots have gained popularity in different kinds of sectors, such as customer service, marketing, sales, e-commerce, e-learning, travel, and even in education itself. This chapter aims to present a chatbot-based approach to learning English as a second language by using computer-assisted language learning systems.